Crime and imprisonment in South Africa with particular reference to prison labour - Corry, Terence Macalaster (Institute of Criminology, 2015)
In this thesis, which records research into prisoner employment practices in various countries and makes certain recommendations for the development of correctional treatment in South Africa, the author has started from the premise that, justifiably or not, imprisonment as a major penal sanction will be with us for the foreseeable future. Furthermore, it is probable that the average length of time being served by prisoners will increase as greater use is made of non-custodial methods of treatment. The treatment of juvenile offenders has been deliberately excluded throughout. Assuming that the aim of imprisonment is to reform/rehabilitate offenders, in addition to keeping them in safe custody, then everything practicable should be done to enhance the possibility of achieving this goal.